HIV/AIDS and other household shocks as catalysts of local commercialization of non‐timber forest products in Southern Africa. (3rd November 2017) - Weyer, D.; Shackleton, C. M.; Adam, Y. O.
Abstract: Local trade in non‐timber forest products (NTFPs) is increasing globally, yet the causes have been little studied. We examine household shock as a driver of NTFP trade in five southern African countries, with an emphasis on HIV/AIDS‐related illness and death. Over the past two years, 95% of trader households experienced at least one shock, with family illness and death recorded for 68% and 42% of households, respectively. Almost 40% had entered the trade because of HIV/AIDS‐related shocks. Additional shocks included natural disasters, crop pests or failure and livestock loss. The sale of NTFPs was the third most common coping strategy, after kinship and agricultural adjustments. Coping strategies differed between sites and type of shock.